Probabilistic linguistics - Bod Rens; Hay Jennifer; Jannedy Stefanie (Cambridge MIT Press, 2003)
This book presents a comprehensive introduction to probabilistic approaches to linguistic inquiry. It covers the application of probabilistic techniques to phonology, morphology, semantics, syntax, language acquation, psycholinguistics, historical lingui
Keywords: Applied statistics; Linguistic analysis; Linguistics-statistical methods; Probabilities